2008
DOI: 10.1007/s10803-008-0610-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in WISC-III Profiles of Children with High-functioning Pervasive Developmental Disorders

Abstract: Using the Japanese version of the Wechsler Intelligence Scale for Children-Third Edition (WISC-III), 26 girls with high-functioning (IQ > or = 70) pervasive developmental disorders (HFPDD) (mean age, 8.2 years) were compared with 116 boys with HFPDD (mean age, 9.0 years). Compared with the boys, the girls scored significantly higher on the Processing Speed index, Coding, and Symbol Search, but scored significantly lower on Block Design. Although both groups showed weakness on Comprehension in the verbal domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
(96 reference statements)
7
25
0
1
Order By: Relevance
“…In general, girls with ASD perform equivalent to TD girls (21) but worse than boys with ASD (20,21). Our findings suggest that girls with ASD are more similar to TD girls than boys with ASD with regard to ATTD.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In general, girls with ASD perform equivalent to TD girls (21) but worse than boys with ASD (20,21). Our findings suggest that girls with ASD are more similar to TD girls than boys with ASD with regard to ATTD.…”
Section: Discussionmentioning
confidence: 55%
“…More recently, using the Block Design (BD) task to test for ATTD, two independent studies reported male superiority for ATTD. Koyama and colleagues (20) reported that females with high functioning ASD (N = 26; mean age = 8.2 years) performed worse on the BD task than males with high functioning ASD (N = 116; mean age = 9.0 years). This finding was also replicated by Bölte and colleagues (21) for a group of high functioning adolescent males (N = 35; mean age = 14.0 years) and females (N = 21; mean age = 14.3 years) with ASD.…”
Section: Sex Differences In Cognition In Autism Samplesmentioning
confidence: 99%
“…Among ASD, there is initial evidence to suggest gender effects on neuropsychological profile (Carter et al 2007;Koyama et al 2009;Koyama et al 2007), and that females may actually exhibit greater cognitive impairment (despite an apparently 'milder' clinical presentation in relation to core features; Lord et al 1982). Other studies, however, have found no such differences (Pilowsky et al 1998;Tsai and Beisler 1983;Volkmar et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…After adolescence, the developmental effects of sexual differences are increased. Adolescents (Holtmann, Bolte, & Poustka, 2007;Koyama, Kamio, Inada, & Kurita, 2009;McLennan et al, 1993) and adults (Lai et al, 2011) have participated in previous studies, yet to the best of our knowledge, in none were male and female subjects with HFASDs restricted to early ages compared. Hsu, Chiang, Lin, and Lin (2012) and Worley and Matson (2011) have emphasized the importance of assessing specific age cohorts.…”
mentioning
confidence: 99%